Usability- and accessibility-focused requirements engineering : first International Workshop, UsARE 2012, held in conjunction with ICSE 2012, Zurich, Switzerland, June 4, 2012 and second International Workshop, UsARE 2014, held in conjunction with RE 2014, Karlskrona, Sweden, August 25, 2014, Revised selected papers /: first International Workshop, UsARE 2012, held in conjunction with ICSE 2012, Zurich, Switzerland, June 4, 2012 and second International Workshop, UsARE 2014, held in conjunction with RE 2014, Karlskrona, Sweden, August 25, 2014, Revised selected papers. (2016) - Unknown
No abstract available